The effect of financial performance on the profit growth of banks listed on the Indonesia Stock Exchange - Verawati, Verawati; Jap, Yustina Peniyanti; Kurniawati, Herni (Global Advances in Business Studies, 2023)
This study aims to provide empirical evidence showing how financial performance affects the profit growth of public sector banks. The sample comprises companies in the banking industry listed on the Indonesia Stock Exchange from 2018–2021. The research considers quantitative data from annual reports produced from 2018–2021 using purposive sampling. This research evaluated financial performance as measured by two proxies: CFROA was found to not affect bank profit growth, while ROE did have an effect. This research is expected to contribute to the development of new proxies for measuring banking financial performance. This research will also help banks focus on maintaining financial ratios according to regulations, such as net profit margin, operating costs and operating income, and non-performing loans. Furthermore, profit growth, as a factor that increases credibility, needs to be considered to maintain banking viability and customer and investor trust.